Two-Year-Olds' Sensitivity to Inflectional Plural Morphology: Allomorphic Effects. Issue 1 (2nd January 2017) - Davies, Benjamin; Xu Rattanasone, Nan; Demuth, Katherine
ABSTRACT: Many English-speaking children use plural nominal forms in spontaneous speech before the age of two, and display some understanding of plural inflection in production tasks. However, results from an intermodal preferential study suggested a lack of comprehension of nominal plural morphology at 24 months of age (Kouider, Halberda, Wood, & Carey, 2006). The goal of the present study was to reexamine this issue using a phonologically and morphologically controlled set of stimuli. The results show that 24-month-olds do demonstrate understanding of nominal plural morphology, but only for the voiceless plural allomorph /s/, not /z/. Further study suggests that this result is not driven by input frequency, but rather by the longer duration of the /s/allomorph, which may enhance its perceptual salience. The implications for learning grammar more generally are discussed.